2014
DOI: 10.1007/s10853-014-8594-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of treatment factors on the properties of bio-apatite materials

Abstract: Animal bones have been studied as a resource of low-crystalline apatite for immobilization of toxic heavy metals. Chemical and thermal treatments can be applied for selective removal of bone organic constituents. In this study, the impact of different treatment factors was determined by experimental design methodology, and comparison of the estimated effects was performed in order to optimize the treatment conditions. Fractional factorial design with five variables at two levels was applied for factors screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…One more very important requirement for CHA coatings is porosity, because bone cells osteoblasts and osteoclasts, also proteins could flow inside pores supporting formation of new bone. The CHA coatings should have a high degree of crystallinity, correct stoichiometry and very good adhesion to the substrate [1,12,13]. Cell colonization and bone growth occur when pores are larger than 50-300 µm [2,11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One more very important requirement for CHA coatings is porosity, because bone cells osteoblasts and osteoclasts, also proteins could flow inside pores supporting formation of new bone. The CHA coatings should have a high degree of crystallinity, correct stoichiometry and very good adhesion to the substrate [1,12,13]. Cell colonization and bone growth occur when pores are larger than 50-300 µm [2,11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Design of experiment (DoE) methods allows measuring the significance of the design variables not only when they are acting alone, but also when combined effects are present [16,17]. DoE based on Plackett-Burman design (PBD) method [18,19] works at two levels and can be constructed on the basis of fractional replication of a full factorial design. It is a powerful and useful tool in searching for the key factors rapidly from a multivariable system and it can provide some important information about each factor by relatively few experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of various treatment conditions on bioapatite properties were compared [20]. Using experimental design methodology, the influence of five process variables was investigated.…”
mentioning
confidence: 99%
“…By simultaneous variation of process variables between lower and higher level, materials with different properties were obtained. Impact of treatment factors was compared by statistical analysis, and it was concluded that annealing had predominant influence on surface properties, as well as sorption capacity towards Cd 2+ [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation